2019
DOI: 10.1186/s40327-019-0068-y
|View full text |Cite
|
Sign up to set email alerts
|

Communication and trust: rethinking the way construction industry professionals and software vendors utilise computer communication mediums

Abstract: Contemporary communication mediums in isolation have reached a technological plateau, proximal communication is no longer limited by spatial or technological constraints. However, integration of communication mediums and their application in pedagogy do not appear to receive the attention they deserve outwith marketing and social psychology research. This is to the determinant of AEC industries where the forefront of proximal communication extends to video conferencing and high latency sharing of open standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…Researchers have investigated user perceptions of AI in different domains [1,33,39], since social perception of one's partner in a collaborative space can impact the outcome of the collaboration. The perceived interactivity -or lack thereof -of systems can have an impact on user perceptions of the system [39] as most existing co-creative systems use one-way communication.…”
Section: Communication In Human-ai Co-creationmentioning
confidence: 99%
“…Researchers have investigated user perceptions of AI in different domains [1,33,39], since social perception of one's partner in a collaborative space can impact the outcome of the collaboration. The perceived interactivity -or lack thereof -of systems can have an impact on user perceptions of the system [39] as most existing co-creative systems use one-way communication.…”
Section: Communication In Human-ai Co-creationmentioning
confidence: 99%
“…Previous research has demonstrated real-time centralised solutions for openBIM [15]. Collectively, these developments are forcing a paradigm shift in design from asynchronous to real-time data exchanges which are impervious to repudiation, ultimately improving inter-organisational perceptions of social presence [24] and imbuing confidence in the design shift expected of openBIM.…”
Section: Introductionmentioning
confidence: 99%
“…There are two categories under types of communication mediums, the physical media, and mechanical media (Oliver, 2019). This has served as the options of our mode of interaction.…”
Section: Introductionmentioning
confidence: 99%